2018
DOI: 10.1080/02813432.2018.1426143
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a student-run clinic in primary care: a mixed-method study with students, patients and supervisors

Abstract: ObjectiveTo explore how a student-run clinic (SRC) in primary health care (PHC) was perceived by students, patients and supervisors.DesignA mixed methods study. Clinical learning environment, supervision and nurse teacher evaluation scale (CLES + T) assessed student satisfaction. Client satisfaction questionnaire-8 (CSQ-8) assessed patient satisfaction. Semi-structured interviews were conducted with supervisors.SettingGustavsberg PHC Center, Stockholm County, Sweden.SubjectsStudents in medicine, nursing, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 25 publications
3
40
0
1
Order By: Relevance
“…Whilst many students continue to learn in regular clinical settings, some settings have been specially adapted to student learning [26]. These have been referred to in the literature as: clinical education wards; interprofessional training wards [710]; dedicated education units [6, 1115]; student training wards [5]; and student-run clinics in primary care [16]. A unified term is lacking, so we use the descriptive term ‘student ward’ to encompass all clinical settings adapted specifically to students.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst many students continue to learn in regular clinical settings, some settings have been specially adapted to student learning [26]. These have been referred to in the literature as: clinical education wards; interprofessional training wards [710]; dedicated education units [6, 1115]; student training wards [5]; and student-run clinics in primary care [16]. A unified term is lacking, so we use the descriptive term ‘student ward’ to encompass all clinical settings adapted specifically to students.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the included studies lacked detailed reporting on the student intervention, there is literature that independently describes the training, supervision and resources required without clinical patient outcomes. For example, Froberg and colleagues detailed the administration, the organisation and the physical environment that students were exposed to when exploring student, patients and supervisor perceptions of participating in a student-run clinic [14]. Nevertheless, one of the included studies [32], recognised this limitation and likewise recommended that future research should investigate and report both patient and student outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This form of evaluation however can only capture the participant's reaction to the service and does not capture higher level evaluation, including the ability of the intervention to facilitate learning and behaviour change [8]. Accordingly, the results from patient satisfaction questionnaires, often suggest that overall patients are satisfied with student services [9][10][11][12][13][14] providing the lowest level of evaluation according to the Kirkpatrick model [8]. Satisfaction may also be influenced by personal factors such as the patient's ability to access healthcare [15] or communication and interpersonal skills of the students.…”
Section: Introductionmentioning
confidence: 99%
“…The services provided by SRCs are supported by the communities they serve, although the number of patients served in such facilities is often unknown. Patients report to be satisfied with the services provided [26][27][28]. While studies have shown that SRCs are valued by both students and patients very little is known of the cost of such services or the cost impact to the healthcare system.…”
Section: Introductionmentioning
confidence: 99%